2017
DOI: 10.1002/humu.23176
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Phenotype Information Aids the Identification of Novel Disease Genes

Abstract: Next-generation sequencing led to the identification of many potential novel disease genes. The presence of mutations in the same gene in multiple unrelated patients is, however, a priori insufficient to establish that these genes are truly involved in the respective disease. Here, we show how phenotype information can be incorporated within statistical approaches to provide additional evidence for the causality of mutations. We developed a broadly applicable statistical model that integrates gene-specific mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It has, for example, been shown that the identification of recurrently mutated genes in individuals with an overlapping phenotype add to the interpretation of variants. This depends, however, on the rarity and specificity of the clinical feature(s) involved [10]. For instance, a combination of rare congenital abnormalities or dysmorphic features is more specific than non-syndromic ID and hypotonia on its own [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has, for example, been shown that the identification of recurrently mutated genes in individuals with an overlapping phenotype add to the interpretation of variants. This depends, however, on the rarity and specificity of the clinical feature(s) involved [10]. For instance, a combination of rare congenital abnormalities or dysmorphic features is more specific than non-syndromic ID and hypotonia on its own [10].…”
Section: Introductionmentioning
confidence: 99%
“…This depends, however, on the rarity and specificity of the clinical feature(s) involved [10]. For instance, a combination of rare congenital abnormalities or dysmorphic features is more specific than non-syndromic ID and hypotonia on its own [10]. Also, the inheritance pattern can be dependent on the severity of the ID and this may help interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…However, hypothesizing a syndrome starting from recognized descriptive clinical criteria allows the clinician to suspect a genetic diagnosis and guide geneticists to choose the technique with the higher diagnostic yield, which is more effective economically and time-saving. Lastly, reverse phenotyping can support molecular findings, confirming the initial hypothesis and establishing the causality of novel or uncertain results (Vulto-van Silfhout et al, 2017). The tetratricopeptide repeat domain-containing protein 5 gene (TTC5) encodes a stress-inducible transcription cofactor that interacts with lysine acetyltransferase p300 and several components of the p300 complex in the nucleus (Demonacos et al, 2001).…”
Section: Introductionmentioning
confidence: 86%